Confined Space and Heterojunction Dual Modulation of ZnO/ZnS for Boosting Photocatalytic CO2 Reduction. Issue 7 (2nd February 2023) - Ma, Xiaohong; Li, Danyang; Xie, Jun; Qi, Jian; Jin, Huacheng; Bai, Liuyang; Zhang, Hao; You, Feifei; Yuan, Fangli
Abstract : The reduction of CO2 to chemical fuel driven by solar energy can not only meet the growing demand for renewable energy, but also balance the carbon cycle in nature. However, the current photocatalysts have low CO2 conversion due to their poor light capture ability, narrow light response range, and high recombination probability of photogenerated carriers. Herein, a heterogeneous photocatalyst of hollow structured ZnO/ZnS decorated with Pt nanoparticles is synthesized through the hydrothermal process and photodeposition method, showing excellent photocatalytic activity for CO2 reduction in long‐time stability and ≈100% CO selectivity, which can mainly contribute to natural enhanced light‐capture ability of the hollow confined space due to multiple reflection and scattering of light in the cavity, thus improving separation efficiency of photogenerated charge carriers due to the type II junction constructed between ZnO and ZnS and the additional reaction active sites after decorating Pt nanoparticles in the surface of the hollow structure. Abstract : The hollow tubular structured ZnO/ZnS decorated with Pt nanoparticles is successfully synthesized toward photocatalytic CO2 reduction, and the optimal sample exhibits excellent CO2 photoreduction activity with CO production rate of 33.26 μmol g −1  h −1, ≈100% selectivity, and excellent durability.